Computationally Guided Design, Synthesis, and Evaluation of Novel Non-Hydroxamic Histone Deacetylase Inhibitors, Based on N-Trifluoroacetamide as a Zinc-Binding Group, Against Breast Cancer - Gerardo Morales-Herrejón; Juan Benjamín García-Vázquez; Cynthia Fernández-Pomares; Norbert Bakalara; José Correa-Basurto; Humberto L. Mendoza-Figueroa (Pharmaceuticals)
Background: Histone deacetylases (HDACs) are enzymes that deacetylate histone proteins, impacting the transcriptional repression and activation of cancer-associated genes such as P53 and Ras. The overexpression of HDACs in breast cancer (BC) underscores their significance as therapeutic targets for modulating gene expression through epigenetic regulation. Methods: In this study, a novel series of SAHA (suberoylanilide hydroxamic acid) analogs were designed using an in silico ligand-based strategy. These analogs were then synthesized and evaluated for their HDAC-inhibitory capacity as well as their antiproliferative capacity on breast cancer cells. These compounds retained an aliphatic LINKER, mimicking the natural substrate acetyl-lysine, while differing from the hydroxamic fragment present in SAHA. Results: The synthesized compounds exhibited HDAC inhibitory activity, suggesting potential for binding to these pharmacological targets. Compounds 5b, 6a, and 6b were identified as promising candidates in the evaluation on breast cancer cell lines MCF-7 and MDA-MB-231 at 72 h. Specifically, compound 6b, which contains an N-trifluoroacetyl group as a zinc-binding group (ZBG), demonstrated an IC50 of 76.7 µM in the MDA-MB-231 cell line and 45.7 µM in the MCF-7 cell line. In the non-tumorigenic cell line, the compound exhibited an IC50 of 154.6 µM. Conversely, SAHA exhibited an almost negligible safety margin with regard to its cytotoxic activity when compared to breast cancer cells and healthy cells (MCF-10A). This observation underscores the elevated toxicity exhibited by hydroxamic acid-derived molecules. Conclusions: The bioisosteric modification of ZBG by N-trifluoroacetyl in 6a and 6b demonstrated favorable cytotoxic activity, exhibiting a higher safety margin. This study underscores the challenge of identifying novel ZBGs to replace hydroxamic acid in the development of HDAC inhibitors, with the objective of enhancing their physicochemical and toxicological profile for utilization in BC treatment.